INFLUENCE OF FUNDAMENTAL FACTORS ON STOCK RETURN LISTED IN JAKARTA ISLAMIC INDEX (JURNAL ECONOMICA : Research of Economic And Economic Education, 2019)
Stock return is the rate of return in a form of repayment from stock trade. This study was conducted to understand the influence of fundamental factor: Current Ratio (CR), Debt to Equity Ratio (DER), Return on Assets (ROA), Price Earning Ratio (PER), and Price to Book Value (PBV) to return stock. Sample in this study is the Jakarta Islamic Index (JII) in Indonesia Stock Exchange (IDX) during the research (2014-2017). Total sample in this study was 17 companies with purposive sampling technique. This study used panel data regression analysis, with some of choosing model Chow test, Hausman test, Lagrange multiplier test, and coefficient test with T-test to test coefficient regression partially, an F-test to test the influence at once with 5% significance rate. The result showed that Current Ratio (CR), Debt to Equity Ratio (DER), Return on Assets (ROA), and Price to Book Value (PBV) has a positive and significant influence to return stock. Meanwhile, Price Earning Ratio (PER) has no significant effect to return stock. But, along with the independent variable, given the influence to return stock of Jakarta Islamic Index (JII) Indonesia Stock Exchange (IDX).